Blast to Freeze : British Art in the 20th Century. - Blair, Tony; Carlake, Margaret; Causey, Andrew; Cork, Richard; Curtis, David; Curtis, Penelope; Harrison, Charles; Hewison, Robert; Howell, Anthony; Hyman, James; Lewison, Jeremy; Livingstone, Marco; et al. (Ostfildern-Ruit : Hatje Cantz Verlag, 2002)
With works by more than one hundred artists, Blast to Freeze follows pioneering trends in the art of Great Britain over the course of a whole century. The publication begins and ends with a decisive break with tradition. On the eve of the First World War, a group of young British artists and writers launched a movement, Vorticism, and a magazine, Blast!, which offered a heady combination of iconoclastic fervour and stylistic innovation deriving from Cubo-Futurist influences. In the 1930s Henry Moore and Barbara Hepworth established a sculptural tradition which was to continue with Anthony Caro, Richard Long and Tony Cragg, down to the present day. The specific character of British Pop Art owes much to its origins in the legendary exhibitions of the Independent Group in the 1950s. But some of the towering figures in British art, such as Stanley Spencer and Francis Bacon, have tended to work in isolation. This large historical span concludes with the Young British Artists who first came to prominence through the exhibition Freeze, organized by Damien Hirst and his friends in 1988. Contributions by the authors provide an in-depth survey of periods, trends, groupings and general topics relating to this eventful century of British art.
Agar, Eileen ; Allington, Edward ; Andrews, Michael ; Annesley, David ; Armitage, Kenneth ; Armstrong, John ; Arnatt, Keith ; Art & Language ; Atkinson, Lawrence ; Auerbach, Frank ; Bacon, Francis ; Banting, John ; Bell, Vanessa ; Blake, Peter ; Bomberg, David ; Boshier, Derek ; Boty, Pauline ; Boyle, Mark ; Brandt, Bill ; Burgin, Victor ; Burra, Edward ; Butler, Reg ; Caro, Anthony ; Caulfield, Patrick ; Chadwick, Lynn ; Charlton, Alan ; Collins, Cecil ; Colquhoun, Ithell ; Cragg, Tony (Anthony) ; Craig-Martin, Michael ; Davie, Alan ; Deacon, Richard ; Demarco, Richard ; Denny, Robyn ; England, Richard ; Epstein, Jacob ; Etchells, Frederick ; Evans, Merlyn ; Fine, Jud ; Finlay, Ian Hamilton ; Flanagan, Barry ; Freud, Lucian ; Fry, Roger ; Gabo, Naum ; Gallaccio, Anya ; Gaudier-Brzeska, Henri ; Gear, William ; Gilbert & George ; Gormley, Antony ; Grant, Duncan ; Hamilton, Richard ; Hamnett, Nina ; Heath, Adrian ; Henderson, Nigel ; Hepworth, Barbara ; Heron, Patrick ; Hill, Anthony ; Hills, Joan ; Hilton, Roger ; Hirst, Damien ; Hockney, David ; Hodgkin, Howard ; Hoyland, John ; Hume, Gary ; Huxley, Paul ; Jennings, Humphrey ; Jones, Allen ; Jones, David ; Joseph, Peter ; Kapoor, Anish ; King, Phillip ; Kitaj, R.B. ; Kossoff, Leon ; Lamb, Henry ; Landy, Michael ; Lanyon, Peter ; Latham, John ; Law, Bob ; Lewis, Wyndham ; Long, Richard ; Maddox, Conroy ; Martin, Kenneth ; Martin, Mary ; McWilliam, F.E. ; Meadows, Bernard ; Mednikoff, Reuben ; Miller, Lee ; Moon, Jeremy ; Moore, Henry ; Nash, Paul ; Nevinson, Christopher ; Nicholson, Ben ; Nicholson, Jim ; Opie, Julian ; Pailthorpe, Grace ; Paolozzi, Eduardo ; Pasmore, Victor ; Penrose, Roland ; Phillips, Peter ; Richards, Ceri ; Riley, Bridget ; Roberts, William ; Saunders, Helen ; Schwitters, Kurt ; Scott, Tim ; etc.
(2 ex. :) Engels (+ Frans)
Blast to Freeze : Britische Kunst im 20. Jahrhundert, Kunstmuseum Wolfsburg, 14. September 2002 - 19 January 2003 ; Blast to Freeze : L'Art Britannique au XXe siècle, les Abattoirs, Toulouse, 24.02.2003 - 11.05.2003.
biog. p. 328-349, bibliog. p. 351-355, biog. auteurs p. 356-357
Engels
Frans
kunstcatalogus
Keywords: Groot-Brittannië